Nilai Konservasi Tinggi Kawasan Hutan Bagi Pelestarian Spesies Mamalia di Supiori, Papua - Freddy Pattiselanno; Rudi A. Maturbongs; Agustina Y.S. Arobaya; Alfredo O. Wanma; Wika Rumbiak (Jurnal Biologi Papua, 2022)
As the definitive regency, Supiori has been separated from Biak Numfor Regency, since 2003. Most of the Supiori Regency area is the Mount Supiori Nature Reserve Area which was stipulated according to the Decree of the Minister of Forestry 525/Kpts/Um/7/82 dated 21 July 1982. In line with the development plan in Supiori, conflicts of interest over the utilisation of forest areas are unavoidable. This has an impact on the condition of existing biodiversity, especially mammalian taxa which are at high risk of being threatened with extinction. Therefore, an assessment of the existence mammalian taxa and their interaction with the potential of forest areas has been carried out using the High Conservation Value - HCV concept approach. Observations were made directly and indirectly on the presence of this mammal species during October 2018. This study succeeded in identifying 16 (sixteen) mammal species belonging to 8 (eight) families that were observed and detected signs of their presence. In accordance with the HCV1 criteria, the forest area in Supiori, both primary forest and secondary forest that has been converted into community plantations, is able to create new habitats for mammal species because there is sufficient food availability there. According to the HCV2 criteria, the observed forest area is still relatively good in supporting the presence of a number of animal species, including groups of mammals. Meanwhile, based on the HCV3 criteria, the karst cave spot in the area is not only a source of water but also a habitat for bats (Emballonura beccarii, Aselliscus tricuspidatus). Considering that most of the area is the area of CA Supiori, the regional development plan for Supiori Regency should provide options for rationalization and changing the status of the area. Therefore, intensive studies need to be carried out to determine which areas in and around the area will be utilized for development activities, and other areas that will be maintained by changing the status of protected areas for the purpose of conserving endemic flora and fauna with high conservation value.